A SOCIOLINGUISTIC AND ANTHROPOLOGICAL EXPLANATION IN THE CULTURAL INSERTION OF THE ASHANINKA DE MARANKIARI BAJO (PERENE) AND PONCHONI (GRAN PAJONAL) - Vílchez Jiménez, Elsa (2002)
The Ashaninka people are the most numerous population of Peruvian Amawn and, thru the years, in spite of the positive or negative different inter-relationships, since the Spanish colony, they keep their own identity. The sociologic and anthropologicfactors ofthe Ashaninka communities of Marankiari Bajo (Perené) and Ponchoni (Gran Pajonal) let us characterize and differentiate their cultural insertion in the national society.